Practical Application for Software Unit Testing of Locomotive Auxiliary Converter Control Platform - WANG Mei; LI Wen-bo; YANG Yin (机车电传动)
Architecture and process of software unit testing in rail transportation field were introduced. With unit testing practice of locomotive auxiliary converter control platform software, decomposition and design of testing process, analysis and statistic of testing results, and evaluation of software quality were completed. Effective improving suggestions was put out, which point the process improvement direction for software engineering.